A THEORETICAL EXAMINATION OF FINANCIAL MODELS OF HIGHER EDUCATION AND PROPOSAL FOR HIGHER EDUCATION IN TÜRKİYE - Erçetin, Şefika Şule; Akbaşlı, Sait; Esen, Seçkin (International Online Journal of Education and Teaching, 2024)
Higher education plays a significant role in the development and growth of a country. It improves the economy of the country and human capital. Higher education is one of the main stages of the educational career of an individual. Every country pays great emphasis on higher education and makes policies to improve the quality and facilities of higher education. The main aim of this paper is to propose a novel and optimal finance model for higher education in Türkiye. We analyze the key features and issues of various financing models of higher education used by different countries in the world. We also evaluate different aspects of financing mechanisms used in different states and the ways through which Türkiye can get an advantage from the experience of other countries. Our proposed financial model aims to assist in improving the quality of research and education in Türkiye as well as reduce the gap between the universities and industry.